Quantification of the Antiplasmodial Alkaloid Carpaine in Papaya (Carica papaya) Leaves - Julianti, Tasqiah; Oufir, Mouhssin; Hamburger, Matthias (Planta Medica, 2014)
Daily consumption of papaya (Carica papaya) leaves as greens and an herbal infusion is common in some parts of Indonesia as a means for preventing malaria. Antiplasmodial activity of the leaf extracts and of the main alkaloid carpaine were recently confirmed. A quantitative assay for determination of carpaine in papaya leaves was developed and validated. The assay involved pressurized liquid extraction and quantification with the aid of ultrahigh-performance liquid chromatography-tandem mass spectroscopy. Extraction conditions were optimized with respect to solvent, temperature, and number of extraction cycles. The ultrahigh-performance liquid chromatography-tandem mass spectroscopy assay was validated over a range of 20–5000 ng/mL (R2 of 0.9908). A total of 29 papaya leaf samples were analyzed, and carpaine concentration in dry leaves was found to range from 0.02 to 0.31 %. No obvious dependence on geographic origin and leaf maturity was observed.
Keywords: carpaine; Carica papaya; Caricaceae; quantification; pressurized liquid extraction; UHPLC-MS/MS